Electromyographic study assessing swallowing function in subacute stroke patients with respiratory muscle weakness. Issue 48 (3rd December 2021) - Liaw, Mei-Yun; Lin, Meng-Chih; Leong, Chau-Peng; Wang, Lin-Yi; Pong, Ya-Ping; Yang, Tsung-Hsun; Huang, Yu-Chi
Abstract: Background: Dysphagia has been reported to be associated with the descent of the hyolaryngeal complex. Further, suprahyoid muscles play a greater role than infrahyoid muscles in elevation of the hyolarngeal complex. Respiratory muscle training (RMT) can improve lung function, and expiratory muscle strength training can facilitate elevation of the hyoid bone and increase the motor unit recruitment of submental muscles during normal swallowing. This study aimed to investigate the surface electromyography (sEMG) of the swallowing muscles, bilaterally, and the effect of RMT on swallowing muscles in stroke patients with respiratory muscle weakness. Methods: Forty patients with first episode of unilateral stroke were included in this retrospective controlled trial. After exclusion of 11 patients with respiratory muscle strength stronger than 70% of the predicted value, 15 were allocated to the RMT group and 14 to the control group. However, eventually, 11 patients in RMT group and 11 patients in control group completed the study. The sEMG of the orbicularis oris, masseter, submental, and infrahyoid muscles were recorded during dry swallowing, water swallowing (2 mL), and forced exhalation against a threshold breathing trainer set at different intensities, at baseline and after 6-week RMT. Results: Regarding the sEMG of submental muscles, there were significant between-group differences on the latency of the unaffected side ( P = .048), significant change from baseline force on the unaffected side ( P = .035), and significant between-side difference ( P = .011) in the RMT group during dry swallowing. Significant change in the duration from baseline was observed on the affected side of the RMT group when blowing was set at 50% maximal expiratory pressure (MEP; P = .015), and on the unaffected side of the control group when blowing set at 15% MEP ( P = .005). Significant difference was observed in the duration between 50% MEP and 15% MEP after 6-week program in the control group ( P = .049). Conclusions: A 6-week RMT can improve the electric signal of the affected swallowing muscles with more effect on the unaffected side than on the affected side during dry swallowing. Furthermore, RMT with 50% MEP rather than 15% MEP can facilitate greater submental muscle activity on the affected side in stroke patients with respiratory muscle weakness.